The authorships and dates of the specific nomina Megophrys shuichengensis and Pseudohynobius shuichengensis (Amphibia) - Ohler, Annemarie; Frétey, Thierry; Dubois, Alain (Zootaxa, 2015)
Two amphibian species from China are designated by the specific nomen shuichengensis, which refers to the Shuicheng County (26°34’N, 104°51’E), south of the city of Liupanshui in the province of Guizhou: Megophrys shuichengensis (Amphibia, Anura) and Pseudohynobius shuichengensis (Amphibia, Urodela). The holotypes (holophoronts) of both species were deposited in Department of Biology of the Liupanshui Teachers Higher College (LTHC below). Both species share the particularity of having been described as new twice, at different dates, in different journals and with different authorships. Although this has been acknowledged for the salamander, it has not yet been so for the frog.